Ebsteins anomaly with constricitve pericarditis (Bangladesh Heart Journal, 2016)
Ebsteins anomaly is a rare congenital cardiac malformation that affects the tricuspid valve commonly, but its association with pericardial disease is even rarer. We report a case of 25 year old man presented with dyspnoea on exertion and fatigability. A diagnosis of Ebsteins anomaly with atrial septal defect (ASD) with constrictive pericarditis was confirmed using transthoracic echocardiography. Peroperatively pericardiotomy was done after meticulous dissection of pericardium. Under cardiopulmonary bypass tricuspid valve was replaced with 29 mm Edward life science porcine tissue heart valve with direct closure of ASD. Patient showed excellent symptomatic improvement and was discharged on 7th POD with advice and after 3 months of follow up patient was doing well post operartive day.Bangladesh Heart Journal 2016; 31(1) : 46-49